Overview of workers hand skin hydration levels on tofu maker at the tofu factory in Matraman district, East Jakarta - Fitri Rahmawati; Linda Julianti Wijayadi; Sari Mariyati Dewi N (Science Midwifery, 2022)
The parameters of human skin health can be assessed from the level of skin hydration. Skin hydration level is the water content in the stratum corneum which is strongly influenced by natural moisturizing factor (NMF) and intercellular lipids. These components can be disrupted when exposed to irritants, such as detergents, too acidic substances, and so on. This condition can cause a decrease in skin hydration levels and becomes inactive, thereby it increases the skin's sensitivity to exogenous factors and infections. Traditional tofu factory workers are workers who have a risk of experiencing a decrease in skin hydration levels due to frequent exposure to tofu-making ingredients with an acidic pH. In Matraman Sub-district, East Jakarta, there are several tofu factories with the manufacturing process that is still processed traditionally. This descriptive observational study with a cross-sectional design aims to determine the overview of hand skin hydration levels in tofu-making workers located in the traditional tofu factory at Matraman District, East Jakarta. So that the workers and factory owners are expected to improve the quality of their workers. Data were obtained by measuring skin hydration levels in 100 study subjects using SK-IV corneometer and filling out questionnaires. Results: an overview of the skin hydration levels of right-handed and left-handed subjects with an average of 20,42% (very dry skin). The average level of skin hydration was lowest in the 60-70 year age group (19,35%), and in the 20-30 year age group (21,65%) and the male group had higher levels (20,59%). Level measurement at the hand location was obtained very dry skin category on the back of the right hand (100%). The more frequent of the frequency exposure to chemicals, the lower the hydration level of the skin (20,08%).